2012
DOI: 10.1590/s0102-695x2012005000041
|View full text |Cite
|
Sign up to set email alerts
|

Studies on trigonelline from Moringa oleifera and its in vitro regulation by feeding precursor in cell cultures

Abstract: Trigonelline (N-methylnicotinate) biosynthesized from nicotinate is one of the metabolically active pyridine alkaloid, widely distributed in plant kingdom. In the present study trigonelline has been isolated from various plant parts and callus cultures of Moringa oleifera Lam., Moringaceae, and was identified using TLC, GLC, GC-MS, which was comparable to that of the standard trigonelline. The trigonelline recovery was found to be maximum in the pods and minimum in flowers. In order to enhance the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Trigonelline has been isolated from various plant parts and callus cultures of M. oleifera Lam., Moringaceae, and was identified using TLC, GLC, GC-MS, which was comparable to that of the standard trigonelline. The trigonelline recovery was found to be maximumin the pods and minimum in flowers (Mathur and Kamal 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Trigonelline has been isolated from various plant parts and callus cultures of M. oleifera Lam., Moringaceae, and was identified using TLC, GLC, GC-MS, which was comparable to that of the standard trigonelline. The trigonelline recovery was found to be maximumin the pods and minimum in flowers (Mathur and Kamal 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Thus, exploring a plant for its bioactive components from different regions of the world, in search of new active principles, always holds significance. There are scanty reports on the identification of metabolites of M. oleifera from Rajasthan, which focus only on pods and in vivo antioxidant activity (Paliwal et al 2011;Mathur and Kamal 2012;Singh et al 2014). The present work was undertaken to investigate and compare the phytochemicals and antioxidant potential of plant parts (Flower, bark and leaves) of M. oleifera from Rajasthan.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of Moringa oleifera performed by Mantur and Kamal 9 using HPLC, different contents (3.55, 2.60, 2.15, 1.90 and 1.60 mg·g -1 ) were found in the pods, leaves, roots, stems and flowers, respectively. Many analytical techniques were employed for the characterization and identification of trigonelline 3,9 . Machado et al 10 observed by NMR spectroscopy a content of 1.20 mg·g -1 of trigonelline in Coffea Arabica roots.…”
Section: Introductionmentioning
confidence: 99%